Speed of adjustment towards target leverage in the ASEAN countries - Chua, Mei Shan; Ab Razak, Nazrul Hisyam; Md Nassir, Annuar; Yahya, Mohamed Hisham (Universiti Malaysia Sarawak, 2021)
This study aims to investigate the speed of adjustment towards target total debt, long-term debt and short-term debt of the Association of South East Asian Nations (ASEAN) namely Malaysia, Singapore, Indonesia and Thailand. The sample of this study included 400 publicly listed firms from 2007 to 2017. Analyses were done with two-step System Generalised Method of Moments (SYS-GMM). Using large sample, the results showed that ASEAN firms are under-adjusted and adjusting with the speed of 30.95%, 37.49% and 40.11% toward total debt, long-term debt and short-term debt, accordingly. To close half of the leverage gap, ASEAN firms need 1.87, 1.62 and 1.35 years for total debt, long-term debt and short-term debt, respectively. The results based on individual country indicated that each country has its own adjustment speed to achieve the target leverage. This study suggests that ASEAN firms are attempting to alter the leverage to its optimum.